New directions in Indian dance - Kothari, Sunil (Mumbai : Marg Foundation, 2003)
Contributed articles on Indian dance forms.
"Vol. 55 No. 2, December, 2003"--T.p. verso.; simultaneously issued in serial format as an issue of Mārg.
Includes index.
Keywords: Dance -- India; Modern dance -- India; Technology and the arts